Social role of economic and financial management in Ecuadorian universities - Mora, Monica Murillo; Espinosa, Maricela Reyes; Perez, Antonio Vaquez (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2018)
The research analyzes the process of emergence and development of the sciences related to economic and financial management worldwide and in Ecuador and highlights the social role of universities in terms of ensuring the new system of financial administration developed by the country, shown the model of interrelation between the three main actors in the Ecuadorian economy where universities have an important role in the economic and financial management linked to the state and the activities that take place in the academy are present, be it teaching or research. The objective of the work lies in knowing the role of Ecuadorian universities in the economic and financial management, the method used in the study was the literature review.